The Modification of Management Cost of Products and Promotion Education in UMKM Cemandi Sidoarjo - Suhartini, Dwi; Tannar, Oryza; Wardana, Muhammad Nugraha Eka; Tiaramurti, Galuh (Nusantara Science and Technology Proceedings, 2020)
Micro, Small, and Medium Enterprises (MSMEs) are informal business organizations that are the driving force of the national economy. The government pays special attention to the development of MSMEs by fostering a conducive business climate environment, providing access to productive resources, strengthening entrepreneurship, and increasing its competitiveness. The purpose of this community service activity is to provide training and assistance to groups of UMKM entrepreneurs in the Sedati sub-district, Sidoarjo regency that produces food and beverages. The problem that is often faced by the MSME sector is the problem of determining the cost of goods, if the determination of the cost of goods is not accurate, it will affect the determination of the selling price. For this reason, training and mentoring is necessary so that entrepreneurs have the knowledge and skills in calculating the cost of production as a basis for determining the selling price. Also, there were problems related to the difficulty of marketing products. This is due to limited access to information and low human resource skills. The results of this service provide evidence that MSME entrepreneurs have not included components of direct labor costs and overhead costs in the production process, such as employee salaries as direct labor costs and overhead costs, such as electricity costs, water costs, telephone costs, equipment depreciation costs. For this reason, MSME entrepreneurs are given training and assistance on how to calculate production costs using the full costing method so that the calculation of production costs is more accurate. The cost of goods obtained will be used as the basis for determining the selling price. Also, they are given training and assistance on digital marketing to provide education and improve skills on how to market their products online so that MSME products are more widely known and can answer business opportunities in the era of industrial revolution 4.0.